2020
DOI: 10.1089/dia.2020.0169
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control in Type 1 Diabetes Mellitus During COVID-19 Quarantine and the Role of In-Home Physical Activity

Abstract: Background: To limit the spread of coronavirus disease 2019 , governments have ordered a series of restrictions that may affect glycemic control in individuals with type 1 diabetes mellitus (T1DM), since physical activity (PA) was not allowed outside home. Methods: We retrospectively evaluated glycemic control of individuals with T1DM using hybrid closed loop (HCL) system in the period before the SARS-CoV-2 outbreak in Italy (February 10-23, 2020-Time 1), when movements were only reduced (February 24-March 8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
149
7
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(175 citation statements)
references
References 10 publications
12
149
7
7
Order By: Relevance
“…We found that participants with a higher PSS-10 score reported worsened glycemic control on SMBG in the preceding 4 weeks. This is in contrast to other studies performed in developed countries that demonstrated no deterioration [24,25], or even an improvement [26] in glycemic control during the lockdown period, attributed to improved self-care. This dissimilarity could possibly be attributed to the differences in the study population.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that participants with a higher PSS-10 score reported worsened glycemic control on SMBG in the preceding 4 weeks. This is in contrast to other studies performed in developed countries that demonstrated no deterioration [24,25], or even an improvement [26] in glycemic control during the lockdown period, attributed to improved self-care. This dissimilarity could possibly be attributed to the differences in the study population.…”
Section: Discussioncontrasting
confidence: 99%
“…In our cohort, the most receptive people seemed to be those with a higher educational level who were less likely to reduce physical activity and younger people because being older than 30 years made the increase in physical activity during home confinement less likely. However a recent study showed that the metabolic control of Type 1 Diabetes in adolescents did not worsen during the restrictions due to COVID-19 pandemics and further improved in those who continued physical activity during the quarantine [ 15 ], demonstrating the power of regular physical activity as an essential strategy for healthy living during the COVID-19 crisis, especially for individuals with chronic diseases. In the present study, only 23% of subjects reported to be affected by a chronic disease and the questionnaire did not investigate the type of the chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Bonora et al [ 13 ] described 33 individuals with T1D using CGM who improved TIR from 54.4 to 65.2% during the lockdown in those who stayed at home, with no changes in those who kept working. Tornese et al [ 14 ] reported 13 adolescents treated with an HCL system and good glycemic control at baseline (TIR 68%), in which glycemic control improved (+ 3%) especially in those who continued physical activity during the lockdown. Recently, Beato [ 15 ] has described the effects of the lockdown in a Spanish population, showing no deleterious effect of the lockdown in a cohort of patients with T1D treated with multiple insulin injections and CGM.…”
Section: Discussionmentioning
confidence: 99%